Baseline evaluation of metal contamination in teleost fishes of the Gulf of Tigullio (north-western Italy): Histopathology and chemical analysis. (April 2019) - Reboa, Anna; Mandich, Alberta; Cutroneo, Laura; Carbone, Cristina; Malatesta, Arianna; Capello, Marco
Abstract: Metals, whether essential (Cu, Zn, Cr, Fe, Mn) or non-essential (Al, As, Cd, Ni, Pb, Hg) for organism metabolism, occur naturally in the marine environment and their abundance can increase due to the presence of human activities. In this study, fish were used as bio-indicators, to determine a correlation between the bio-accumulation of metals in muscle and gill tissues and the health status of fish. The study area was the Gulf of Tigullio (north-western Italy), which is impacted by various sources of metal contamination. Histopathology served as a significant tool to investigate possible alterations in gills, one of the main organs involved in fish physiology. Results highlighted some correlations between certain metals (e.g. Pb, Ni) and gill alterations (e.g. epithelial hyperplasia, epithelial lifting), providing baseline data from a pool of different fish species, which can be used for comparison purposes in further studies. Highlights: A pool of different sea fish species was used as bio-indicators for metal pollution. High metal concentrations in gills showed correlation with some gill alterations. Histopathology is a useful monitoring tool to investigate alterations in gills. Cd, Hg and Pb values in muscle tissue were often higher than legislation limits.